OP119 Advanced Therapy Medicinal Products: Are Current Health Technology Assessment Methods Suitable?. (2017) - Hampson, Grace; Towse, Adrian
Abstract : INTRODUCTION: There is considerable excitement around the development of regenerative medicines (or advanced therapy medicinal products, ATMPs), with the expectation that they may bring substantial clinical gains and offer cures for previous debilitating and fatal diseases. However, high costs mean that Health Technology Assessment (HTA) and reimbursement decisions are challenging for payers and manufacturers, even when the therapies are expected to offer good value for money. In Europe, seven ATMPs have market authorization, yet only one has achieved national level reimbursement. Statistics such as these put HTA bodies under pressure to review their methods and consider how these can apply to regenerative medicines. METHODS: We present a review of one example, from the United Kingdom's National Institute for Health and Care Excellence (NICE), who commissioned an external organization to undertake a mock appraisal of a hypothetical ATMP using standard methods. The therapeutic area chosen for the mock appraisal was chimeric antigen receptor (CAR) T-cell therapy for treating relapsed or refractory B-cell acute lymphoblastic leukaemia. RESULTS: The role of uncertainty was a key consideration within the report, yet we found that the presentation of uncertainty within the mock appraisal was misleading for decision makers. We found that the exercise represents a thorough mock HTA of CAR T-cell therapy. However, it focused on testing whether ATMPs could fit into the existing HTA pathway for conventional medicines, rather than seeking to identify the most suitable approach for assessing regenerative medicines. We suggest the latter would have been a more relevant question for the mock appraisal. CONCLUSIONS: Any significant departures from the usual HTA process must be based on solid economic rationale if we are to ensure efficient allocation of resources. Thus, in order for regenerative medicines to be given 'special treatment, ' it must be demonstrated that societal preferences, or the full extent of health (or non-health) benefits, are not being realised for this group of treatments through existing HTA methods.